The Implementation of 13 Curriculum of Physical Education, Sports and Health at the Seventh Grade Students of SMP Negeri 6 Makassar - Nurhikmah, Nurhikmah; Ramli, Abdul Malik; Sujarwo, Sujarwo; Akhiruddin, Akhiruddin; Iskandar, Abd. Malik (International Journal for Educational and Vocational Studies, 2019)
Curriculum is all activities that given to students under school responsibility. So that curriculum is not limited to the activities in the classroom, but also outside in the classroom. The purpose of this study was to find out the Implementation of the 2013 curriculum at the VII grade physical, sports and health education subjects of SMP Negeri Makassar. Data sources were primary and secondary data. Kind of research was descriptive qualitative research, namely it described qualitatively related to the curriculum, especially the implementation of the 2013 curriculum in physical,  sports and health  education  subjects which started from beginning, main and closing activities have been carried out properly with reference to the scientific approach with five components that is, observing, asking, exploring and associating, but the main activities of exploring and associating were not carried out, because sports physical education and healthsubjects were more practice oriented in the field so that the two scientific stages are considered not in accordance with the characteristics of PJOK subjects that already have rules standard in doing movements. Whereas the implementation of assessors was more dominant using a skill test in performing motoric movements which was 70%, while the written assessment was only 30%.